THE ECONOMIC ASPECT OF THE KAZAKH-TURKISH RELATIONS - Л.Н., Нурсултaновa; Т.Е., Өтегеновa (Journal of Oriental Studies, 2019)
In the article considered trade and economic relations between the two countries at the present stage. It should be noted that Turkey is expanding its presence not only in Kazakhstan, but also in Central Asia. Turkish business operates in various sectors of the Kazakhstan economy. Bilateral relations have positive dynamics and a strategic outlook. Key words: Kazakhstan, Turkey, economic ties, investments.